Culture notes in "˜Bahasaku 1: Ayo bicara bahasa Indonesia' - Sahasti, Julananda Putri (Diksi, 2023)
Language and culture are two things that are closely related to each other. The purpose of this study is to describe the cultural notes presented in the book "Bahasaku 1: Ayo Bicara Bahasa Indonesia". The research method used in this study is descriptive qualitative with a content analysis approach. The data source in this study was the book 'Bahasaku 1: Ayo Bicara Bahasa Indonesia' compiled by the Indonesian Language Institute Kursul Alam, Yogyakarta. Data were analyzed in five stages, namely compiling notes, disassembling data, rearranging based on data, interpreting, and drawing conclusions. Based on the results of the data analyses, it can be concluded that the cultural notes in the book My Language 1: Let's Talk Indonesian can be grouped into eight categories, namely: 1) greetings; 2) eating habits; 3) rubber watch; 4) small talks; 5) mudik; 6) coutercies of guests and hosts; 7) beach suits and the myth of Nyai Roro Kidul; and 8) 'kiri' in the context of public transportation. The cultural notes in the book "Bahasaku 1: Ayo Bicara Bahasa Indonesia" belonging to Alam Bahasa Indonesia have been well organized. The cultural notes in this textbook are not only specifically listed in the "Cultural Notes" section at the end of each lesson, but, they are also integrated well into every text in the lesson. My language book 1 contains clear concepts and understandings that can accurately describe the cultures that have developed in the Indonesian society.Keywords: culture notes, textbook, foreign language, cultural understanding, BIPA